Aglomerasi Perkotaan di Daerah Istimewa Yogyakarta - Mudrajad Kuncoro (Universitas Islam Indonesia, 2006)
Agglomeration has become a central attention in the literature of economic geography, business strategy and national competitiveness, and regional studies. However, we still know little of how common and widespread the phenomenon of agglomeration across regions, cities, and industries.This paper explores the nature of agglomeration, where it tends to locate in DIY, and the driving forces underpinning agglomeration. It found that urbanisation and industrialisation tend to merge and form an extended city of Yogyakarta. The pattern and dynamics of agglomeration has been extending, albeit bringing wider inequality spatially. Hence, a common